KAJIAN ADAPTASI KIJING PILSBRYOCONCHA EXILIS SEBAGAI LANGKAH AWAL PEMANFAATANNYA DALAM BIOFILTRASI PENCEMAR ORGANIK DI PERAIRAN WADUK - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2006)
Pilsbryoconcha exilis is freshwater mussel that derive its feed throughfiltering water. The mussels could filter such as phytoplankton andsuspended material to get their feed. Its ability may be used in waterremediation which is polluted by organic contaminant, such as at Ciratareservoir in West JavaTo undesrtand that freshwater mussels have abilityto adapt in Cirata reservoir, a group of mussels kept in certain watercolumn at some station observation. Then mussels growth rate wasmeasured. Research result indicated that freshwater mussel could beadapted and grown in different water column as well as in their habitat(bottom sediment with muddy substrate). The mussels planted in Ciratareservoir have relation length and weight pattern which categorize asnegative allo-metric (increasing of length is more dominant than weight).Observation result of mussels grow at Jangari Station was remarked bycoefficient of growth (k=0.47) and infinity of length ( 8 =9.41); at Pasir Empul k=0.64 and L8 =9.62; at Jati Nenggang k=0.47 and L8 =9.41; also atmussels stock cages k=0.65 dan L8 =9.62. The result of this study concluded that mussels could be grown in Cirata reservoir of West Java.